Purpose, practice, and pedagogy in rhetorical criticism - Kuypers, Jim A. (Lexington studies in political communication., 2014)
Purpose, Practice, and Pedagogy in Rhetorical Criticism brings together fifteen rhetorical critics who address contemporary issues in criticism by answering three key questions: What is the purpose of rhetorical criticism? How do you practice rhetorical criticism? How do you teach rhetorical criticism? The book serves as both guide and resource in all three areas, presenting personal perspectives from top rhetorical critics.